PLANNING INTERNAL AUDIT IN BUDGET ORGANIZATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article talks about the purpose of conducting an internal audit, the development of an effective system, and the issues that are required to be considered in this process. In addition, in this article, the author analyzed the procedure for reporting on the internal audit.